Ultrastructural Transformations in Bean Inner Mitochondrial Membranes - Wilson, R. H. (1973)
The ultrastructure of inner membrane-matrix mitochondria isolated from bean (Phaseolus vulgaris) shoots was examined in different metabolic states. Gross ultrastructural transformations analogous to the condensed-to-orthodox configurational changes reported in mammalian mitochondria are observed on transistion from nonrespiring to respiring metabolism. With the induction of oxidative phosphorylation, the particles remain in the orthodox configurational state. The reverse orthodox-to-condensed configurational changes observed in mammalian preparations does not occur. Optically monitored absorbancy studies with bean particles show a substrate-supported P(i)-induced swelling under the same conditions that induce the condensed-to-orthodox ultrastructural transformation. The swelling is associated with the net uptake of K(+) and P(i) as well as a small P(i)-induced respiratory stimulation. When phosphorylation is initiated with these swollen particles, the optically monitored volume remains unchanged. Thus a positive correlation exists between the ultrastructural configuration and the osmotic volume changes, which supports the conclusion that configurational changes reflect internal osmotic adjustments.